Development of Peer Educators as the Empowerment of Santri Husada in Islamic Boarding Schools Towards a Healthy and Marriage Age Maturity (PUP) - Mursyidul Ibad; Dwi Handayani; Kuuni Ulfah Naila El Muna (UNUSA Press, 2025)
Marriage is conducted with the aim of establishing a household between partners, requiring maturity and responsibility both physically and mentally. According to the 2017 Indonesian Demographic and Health Survey (SDKI) for East Java Province, 17 percent of women of reproductive age (20–24 years) were married by the age of 18, while two percent reported marrying at the age of 15. Islamic boarding schools (Pesantren) face similar issues regarding early marriage. Many students are forced to drop out of both formal schools and Pesantren due to the constraints of a still conservative socio-cultural environment. The community service program was conducted from May to September 2024 at Pondok Pesantren X, located in Krembung District, Sidoarjo Regency. A total of 17 Santri Husada participated in the activities. Strengthening the role of Santri Husada and improving their knowledge and attitudes toward the maturation of marriage age (Pendewasaan Usia Perkawinan or PUP) are essential. Education through peer educators has been shown to positively impact Santri Husada knowledge on stunting (88.2%), reproductive health (82.4%), and the maturation of marriage age (88.2%). Additionally, this initiative has encouraged behavioral changes among students, particularly in managing the cleanliness and organization of their sleeping environment.